PTU-075 What is the benefit of telephone and virtual IBD clinics in a DGH?. (8th June 2018) - Al-Hillawi, Lulia; Blaker, Paul; Harris, Adam; Gurung, Bikash; Bedwell, Theresa; McEnery, Catriona; Warner, Eleanor
Abstract : Introduction: Inflammatory Bowel Disease (IBD) services across the UK are under increasing pressure. To improve efficiency, pathways of care have been proposed. However these are difficult to cost due to a lack of data on current service provision, leading to challenges with commissioning. We set out to characterise our IBD service in a District General Hospital (DGH) setting, having recently implemented a new pathway to streamline the service. A second aim was to establish if our service met the NICE quality standard of seeing IBD referrals within 4 weeks. Methods: Prospective data from clinics at two DGHs were gathered from 92 patient journeys over 52 weeks. The activity of a new IBD helpline was analysed over a 28 week period and outcomes prospectively recorded. Specifically the activity avoided as a result of the helpline was analysed and costed. Finally, the outcomes from a new virtual IBD clinic were prospectively collected over a 10 week period. Results: 33% of clinic patients had IBD, of which 59% were in remission. 41% of patients were felt suitable for non-clinic follow-up. 76% were interested in the concept of 'self-management' during remission. 95% of patients rated the consultation experience as 'good' or 'very good'. There was an average 1 new to 4 follow-up encounters within the first year from referral; 26% were successfully conducted by telephone. Median time from initial referral to first outpatient contact was 9.1 weeks (4.9–19.9). 58% were not seen within 4 weeks of referral. The IBD helpline received 543 calls in 28 weeks (average 83/month). The interventions avoided due to this service were; 156 GP consultations, 231 outpatient reviews, 39 ED attendances and 6 admissions. Estimated cost saving due to activity avoided was £37, 913, with helpline costs of £2065. 92% of patients rated the helpline as 'good' or 'very good'. 100% of patients reported a response within 24 hours (weekdays). Since September 2017, 10 virtual IBD clinics have led to 191 treatment decisions. High cost biologic drugs have been stopped in 7 patients, without having to wait for face-to-face review, with an estimated saving of £12 300. 59 patients were identified as needing annual review and 51 identified as needing urgent treatment decisions. Overall quantifiable cost savings from the helpline and virtual clinic totalled £11, 000/month. Conclusions: Telephone and virtual clinics result in earlier treatment decisions for IBD patients and give quantifiable cost savings as part of an IBD pathway at a DGH. By increasing virtual clinics and encouraging patient autonomy, we can aim to improve the NICE quality standard of seeing new IBD patients within 4 weeks of referral. Improving autonomy over services for both clinician and patient can allow for more efficient IBD care.